2016
DOI: 10.2106/jbjs.15.01119
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistencies Between Physician-Reported Disclosures at the AAOS Annual Meeting and Industry-Reported Financial Disclosures in the Open Payments Database

Abstract: ,"Inconsistencies between physician-reported disclosures at the AAOS annual meeting and industry-reported financial disclosures in the open payments database." The Journal of Bone and Joint Surgery.98,20. e90. (2016 Background: The purpose of this study was to determine the rate and type of inconsistencies between disclosures self-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 27 publications
(29 reference statements)
1
33
0
Order By: Relevance
“…However, for all journals, potential editorial conflicts of interest are only identified by editor self report, and previous studies have shown self report of conflicts of interest to have considerable shortcomings. 53 54 55 56 57 While editors may not believe that financial payments from industry influence their judgments, there is evidence to suggest that all individuals are subject to subconscious bias from many kinds of influences that are much more subtle than money, the impact of which may be even more difficult to ascertain and self report. 13 15 …”
Section: Discussionmentioning
confidence: 99%
“…However, for all journals, potential editorial conflicts of interest are only identified by editor self report, and previous studies have shown self report of conflicts of interest to have considerable shortcomings. 53 54 55 56 57 While editors may not believe that financial payments from industry influence their judgments, there is evidence to suggest that all individuals are subject to subconscious bias from many kinds of influences that are much more subtle than money, the impact of which may be even more difficult to ascertain and self report. 13 15 …”
Section: Discussionmentioning
confidence: 99%
“…Other studies of payments to orthopaedic surgeons from industry sources based on the OPD were somewhat limited in that they described only the data set, 11,23,27 did not assess accuracy of self-disclosures, 11,21 or assessed the accuracy of nonpublication self-disclosures (eg, disclosures from orthopaedic conferences). 14 Relatively little is known about the accuracy of conflict of interest disclosures among high-impact factor orthopaedic journals. The American Journal of Sports Medicine (AJSM) has the highest 5-year impact factor in orthopaedic surgery and is distributed to a wide readership involved in various aspects of sports medicine and musculoskeletal health care delivery.…”
mentioning
confidence: 99%
“…Other studies of payments to orthopaedic surgeons from industry sources based on the OPD were somewhat limited in that they described only the data set, 11,23,27 did not assess accuracy of self-disclosures, 11,21 or assessed the accuracy of nonpublication self-disclosures (eg, disclosures from orthopaedic conferences). 14…”
mentioning
confidence: 99%
“…11 Even after the passage of the PPSA, 1 study demonstrated a 35% rate of inconsistency when disclosures from presenters at the 2014 AAOS National Meeting were compared with the Open Payments database. 8 Studies also have demonstrated variability between surgeon-reported disclosures and industry-reported payments in the spine and trauma subspecialties. 3,15 A recent study demonstrated that 82.9% of authors publishing in The American Journal of Sports Medicine had discrepancies between disclosures that they self-reported to the journal and industry-reported disclosures found in the Open Payments database.…”
Section: Discussionmentioning
confidence: 99%